2004
DOI: 10.2746/0425164044864660
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation: normal values of magnetic motor evoked potentials in 84 normal horses and influence of height, weight, age and sex

Abstract: Reasons for performing study: Cervical spinal corddysfunction is a common problem in equine medicine and the currently available tests give no objective information about the functionality of the nervous tracts. Therefore, transcranial magnetic stimulation (TMS) was performed in 84 healthy horses of different height in order to have an objective measure for the integrity of the descending motor tracts in normal horses. Objectives: To obtain reference values for onset latency and peak-to-peak amplitude of magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 57 publications
5
45
1
1
Order By: Relevance
“…A longer neuronal path length means that the impulse will need to travel a larger distance before reaching the muscle and generating a motor evoked potential; thus, yielding longer latencies. The influence of body size on TMMEPs latencies has also been reported in humans and horses (Chu, 1989; Nollet et al, 2004). These results indicate that reference ranges for TMMEPs latency will likely be different across dog breeds with different body sizes.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A longer neuronal path length means that the impulse will need to travel a larger distance before reaching the muscle and generating a motor evoked potential; thus, yielding longer latencies. The influence of body size on TMMEPs latencies has also been reported in humans and horses (Chu, 1989; Nollet et al, 2004). These results indicate that reference ranges for TMMEPs latency will likely be different across dog breeds with different body sizes.…”
Section: Discussionmentioning
confidence: 69%
“…However, no study has reported TMMEPs values in clinically normal GDs or investigated its use in GDs with CSM. In humans and horses, TMMEPs latencies are influenced by body size (Chu, 1989; Nollet et al, 2004). GDs are larger than Doberman Pinschers; thus, TMMEPs reference ranges obtained in Doberman Pinschers may not apply to GDs.…”
Section: Introductionmentioning
confidence: 99%
“…This method has recently been validated and used to distinguish motor tract disorders from other causes of recumbency in clinical cases. [76][77][78] …”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…Transcranial magnetic stimulation (TMS) with recording of magnetic motor evoked potentials (MMEP) is a promising additional test for diagnosis of spinal cord dysfunctions in horses . A magnetic 70 mm coil is placed on the head of the horse, at the level of the brain, to perform a magnetic stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…This induces descending volleys through the spinal cord, evoking a muscle contraction reflected by the MMEP on the electromyography (EMG) machine. On each MMEP, the latency time, the time between stimulation and onset of muscle contraction, can be measured, which is the most reliable variable . In horses, the mean latency time of 4 MMEP is used, instead of the minimal latency time which is used in humans.…”
Section: Introductionmentioning
confidence: 99%